EP32 Seamless transition to a biosimilar. (20th April 2020) - Wood, Katherine; Pickersgill, Gemma; Khoffash, Mahmoud Al; Stevens, Robert; Coote, Annabel; Sekyrynskaya, Helen; Mackenzie, Felicity; Yee, Chee-Seng
Abstract: Background: As adalimumab biosimilars were about to be launched in the UK, our trust was looking for ways to simplify and streamline the process to make it an efficient and seamless transition from originator to biosimilar. Consultations took place between all the stakeholders (clinical commissioning groups, pharmacy department, rheumatology department, home-care provider and biosimilar manufacturer) and an agreement was reached as follows: letters were sent to patients explaining what a biosimilar is and the process of transition. A helpline was established whereby patients were advised to contact if they had any questions or concerns. The home-care provider provided pre-populated prescriptions for the biosimilar. Latex allergy was determined for each patient and transition was made at next delivery (patients with a latex allergy stayed on originator as biosimilar pen contains latex). There was no additional clinic visit required. This is a descriptive analysis of our experience using this seamless transition to the biosimilar adalimumab. Methods: From our database, we collected demographic data on the rheumatology patients who were on the originator and those who transitioned to the biosimilar. The success of the transition was determined if patients remained on the biosimilar six months later. In patients who did not remain on the biosimilar at six months, we analysed if the patient had switched back to originator, to a different targeted therapy or no longer on a targeted therapy. Results: There were 262 rheumatology patients on the originator and 2 patients had a latex allergy. Therefore 260 patients were transitioned during a two month period. They were 50.4% female with mean age of 54 years (range 22 to 86 years) and the majority were Caucasians (99%). The diagnoses for this population were axial spondyloarthropathy (45%), rheumatoid arthritis (33%), psoriatic arthritis (21%) and juvenile idiopathic arthritis (1%). At six months post transition, 18 patients (6.9%) were no longer on the biosimilar: 57.1% female, mean age 50 (range 23 to 73), 85.7% axial spondyloarthropathy and all Caucasian. Of these, 11 had switched back to the originator, 3 were switched to a different targeted therapy and 4 were no longer on targeted therapy. The reasons for switching back to the originator were worsening symptoms (6 patients), side effects (4 patients) and difficulty using the pen device (1 patient). Conclusion: This seamless transition with minimal impact on clinical time was very successful (93.1% success). It will be the model to be used for the future transition of other biosimilars. Disclosures: K. Wood None. G. Pickersgill None. M. Al Khoffash None. R. Stevens None. A. Coote None. H. Sekyrynskaya None. F. Mackenzie None. C. Yee None.